(untitled) (Al-Wasatiyah: Journal of Religious Moderation, 2024)
This study emphasizes the importance of respecting local traditions to achieve religious harmony by examining how the role of local traditions shapes harmony as an indicator of religious moderation. The form of this research is literature and includes qualitative research from books on religious moderation of the Ministry of Religious Affairs and periodicals such as research journals as data materials that are still related to the research topic. The results of the study indicate that local traditions have deep significance in the social context of Indonesia, acting as a glue for cultural identity, fostering harmony among diverse groups, and strengthening a sense of togetherness among various ethnic and religious groups. In strengthening harmony through tradition as an indicator of religious moderation, there are several approaches. First. Tolerance. Second. Respect for religious and cultural diversity. Third. Applying local traditional values. Fourth. Effective communication. Through these approaches, it is hoped that local traditions in Indonesia will not only reflect an extraordinary cultural richness but also contribute to the formation of social identity and harmony among religions.